SB-T-121205, a next-generation taxane, enhances apoptosis and inhibits migration/invasion in MCF-7/PTX cells - Zheng, Xiaowei (Int J Oncol, 2017)
Breast cancer is the leading cause of cancer death among women. Paclitaxel, a mitotic inhibitor, is highly effective in the treatment of breast cancer. However, development of resistance to paclitaxel limits its clinical use. Identifying new compounds and new strategies that are effective against breast cancer, in particular drug-resistant cancer, is of great importance. The aim of the present study was to explore the potential of a next-generation taxoid, SB-T-121205, in modulating the proliferation, migration and invasion of paclitaxel-resistant human breast cancer cells (MCF-7/PTX) and further evaluate the underlying molecular mechanisms. The results of MTT assay showed that SB-T-121205 has much higher potency to human breast cancer cells (MCF-7/S, MCF-7/PTX and MDA-MB-453 cells) than paclitaxel, while that the non-tumorigenic human bronchial epithelial cells (BEAS-2B) were slightly less sensitive to SB-T-121205 than paclitaxel. Flow cytometry and western blot methods revealed that SB-T-121205 induced cell cycle arrest at the G2/M phase and apoptosis in MCF-7/PTX cells through accelerating mitochondrial apoptotic pathway, resulting in reduction of Bcl-2/Bax ratio, as well as elevation of caspase-3, caspase-9, and poly(ADP-ribose) polymerase (PARP) levels. Moreover, SB-T-121205 changed epithelial-mesenchymal transition (EMT) property, and suppressed migration and invasion abilities of MCF-7/PTX cells. Additionally, SB-T-121205 exerted antitumor activity by inhibiting the transgelin 2 and PI3K/Akt pathway. These findings indicate that SB-T-121205 is a potent antitumor agent that promotes apoptosis and also recedes migration/invasion abilities of MCF-7/PTX cells by restraining the activity of transgelin 2 and PI3K/Akt, as well as mitochondrial apoptotic pathway. Such results suggest a potential clinical value of SB-T-121205 in breast cancer treatment.